2019
DOI: 10.1111/lam.13129
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐biofilm and cytoprotective activities of quercetin againstPseudomonas aeruginosaisolates

Abstract: Increase in infection with multidrug resistant Pseudomonas aeruginosa is a serious global challenge in healthcare. Pseudomonas aeruginosa is capable of causing human infection in various sites and complicates the infection due to its virulence factors. This study was aimed to investigate the effect of quercetin, a dietary flavonoid against the virulence factors of P. aeruginosa and its cell protective effects on epithelial cells. Bactericidal activity, anti‐biofilm activity and effect on different virulence fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Moreover, quercetin seems to restore corticosteroid sensitivity in cells from COPD patients by activation of the adenosine monophosphate-activated protein kinase (AMPK) [62], and a community clinical trial showed a reduction of upper respiratory tract infection total sick days and severity in middle age and older subjects ingesting 1000 mg quercetin/day for 12 weeks [63]. Quercetin antimicrobial effect has been previously reported [64][65][66] but, to our knowledge, this is the first study assessing its antimicrobial activity against H. influenzae.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, quercetin seems to restore corticosteroid sensitivity in cells from COPD patients by activation of the adenosine monophosphate-activated protein kinase (AMPK) [62], and a community clinical trial showed a reduction of upper respiratory tract infection total sick days and severity in middle age and older subjects ingesting 1000 mg quercetin/day for 12 weeks [63]. Quercetin antimicrobial effect has been previously reported [64][65][66] but, to our knowledge, this is the first study assessing its antimicrobial activity against H. influenzae.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies demonstrated that quercetin can alter the cell surface properties to inhibit biofilm formation 41 43 . Thus, we assessed the cell surface properties by cell surface hydrophobicity and aggregation assays.…”
Section: Discussionmentioning
confidence: 99%
“…For infection studies, HEK 293T cells were seeded onto 96-well plates (10,000 cells/well) in DMEM without the antibiotics and infected with the bacteria at a multiplicity of infection (MOI) of 10 for 3 h at 37 °C. Bacterial attachment to the HEK cells was estimated by the plate count method described earlier [ 50 ]. Briefly, the cells were washed with PBS, homogenized, serially diluted, and plated on NA.…”
Section: Methodsmentioning
confidence: 99%